Hepatitis B viral infection and its common genotype circulation: A molecular approach - Asad Ullah Khan; Mujaddad Ur Rehman; Muhammad Ikram; Muhammad Zahoor; Azam Hayat; Renald Blundell (The Microbe)
Hepatitis B virus (HBV) is the causes of liver infection and associated with cirrhosis, carcinoma, and fibrosis of liver. In this research study, we conducted an observational study to evaluate the distribution of HBV infection and its genotypes in selected cities of Khyber Pakhtunkhwa, Pakistan. A total of 426 samples were collected from selected cities of Khyber Pakhtunkhwa. Mardan (n = 163), Dir (Lower) (n = 116), Malakand (n = 53), Miran Shah (n = 29), Dera Ismail Khan (n = 28), Swat (n = 22), and Hangu (n = 15). For molecular identification of hepatitis B virus infection, the ICT (Immunochromatographic techniques) kits were used for the Screening of Hepatitis B virus infection among general population. The positive samples of ICT test were further subjected to Real-time Polymerase chain reaction (PCR), of which 282 (66.2 %) were males, and 144 (33.8 %) were females. Out of 426 ICT kit positive samples, 218 (51.18 %) were found PCR positive. The maximum number of positive cases, 157 (36.86 %), was found between 15 and 34 years. Sixty samples were further processed for HBV genotyping. A mixed genotype was detected in 29 (48.3 %) individuals, followed by genotype D in 23 (38.3 %) and untypable in 8 (13.3 %). The positivity rate of HBV was recorded high among males compared to females. Most patients who reported positive for HBV were co-infected with two genotypes. This research will help to provide background information to government and health authorities to raise public awareness and improve the capacity of the healthcare delivery system for hepatitis B virus infection.